Pour une économie sociale sans rivages : Jacques Moreau (1927-2004). Hommage - Chomel, André (1924-....); Alix, Nicole; Gueslin, André; Moreau, Jacques (1927-2004); Fondation d'entreprise Crédit coopératif
graph., couv. ill. en coul. Bibliogr. p. 167-168